Simultaneous Morscher's osteotomy and arthroscopic debridement in the management of Legg–Calvé–Perthes disease: a case report and literature review. (23rd June 2021) - Bosakhar, Batool; Baldawi, Hassan; Liu, Kathy; Ayeni, Olufemi R; Kishta, Waleed
Abstract: There is a lack of consensus around optimal surgical management for Legg–Calvé–Perthes Disease (LCPD). This case report discusses the benefits of combining arthroscopic femoral neck osteochondroplasty and labral repair with Morscher's Osteotomy (MO) for LCPD. S.A. is a 17-year-old female diagnosed with LCPD at the age of 6 years and has long-standing right hip symptoms. An arthroscopic femoral neck osteochondroplasty and labral repair followed by MO was performed. The pre-operative and 8 months post-operative International Hip Outcome Tool (iHOT-12) scores were 16.3 and 79.8 out of 100, respectively, indicating better quality-of-life. Also, the femoral neck-shaft-angle (NSA) changed from 120 pre-operative to 138.7 post-operative to represent the correction of coxa vara. The literature review revealed no published reports describing combined MO with hip arthroscopic interventions in managing LCPD. Combined arthroscopic femoral neck osteochondroplasty (with labral repair) and MO provides high patient satisfaction and improves radiographic parameters in patients with LCPD.